The conservation and integration of immigrant communities: the military dependants’ villages in Taiwan - Lu, Yin-Chao (2017)
In general, one of the significant aims of conservation for a historical settlement is saving the authentic physical settings and presenting the residents’ culture to the public for reproducing the sense of the place and to pass down its culture to next generations. As same as the fact that it is impossible to retain every perspective of history; in practical aspects of heritage conservation, it is impossible to protect and demonstrate everything of a place. The different selections of historical materials variously describe historical stories, memories and the meanings of a place. On a conserved historical site, the conservation strategies and practices and visitors’ experiences construct the presented narratives of the place. However, still a lot of narratives that offer other meanings of the place are neglected.